2020
DOI: 10.1007/s12471-020-01413-1
|View full text |Cite
|
Sign up to set email alerts
|

Patients who do not complete cardiac rehabilitation have an increased risk of cardiovascular events during long-term follow-up

Abstract: Background Cardiac rehabilitation (CR) has favourable effects on cardiovascular mortality and morbidity. Therefore, it might reasonable to expect that incomplete CR participation will result in suboptimal patient outcomes. Methods We studied the 914 post-acute coronary syndrome patients who participated in the OPTImal CArdiac REhabilitation (OPTICARE) trial. They all started a 'standard' CR programme, with physical exercises (group sessions) twice a week for 12 weeks. Incomplete CR was defined as participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Inotrope was given in 36 cases (72%). Mainly 66% of cases were kept on mechanical ventilation; out of that 21 on intermittent positive-pressure ventilation (IPPV) and 12 on BIPAP (Bi-level Positi- This cohort presented to hospital in 9 hours compared to Van den Berg, et al [17,18] study which quotes duration of 3.5 hours. In our study 82% of patients presented before 12 hours of onset of symptoms which reflects increase in awareness of patients.…”
Section: Discussionmentioning
confidence: 94%
“…Inotrope was given in 36 cases (72%). Mainly 66% of cases were kept on mechanical ventilation; out of that 21 on intermittent positive-pressure ventilation (IPPV) and 12 on BIPAP (Bi-level Positi- This cohort presented to hospital in 9 hours compared to Van den Berg, et al [17,18] study which quotes duration of 3.5 hours. In our study 82% of patients presented before 12 hours of onset of symptoms which reflects increase in awareness of patients.…”
Section: Discussionmentioning
confidence: 94%
“…Dropout is associated with unfavourable outcomes, as reported by Sunamura et al. in this issue [ 5 ]. Premature termination of the CR programme represents a loss of benefits, a waste of resources and a waste of the limited capacity for CR.…”
mentioning
confidence: 79%
“…The rehabilitation program benefits are gained from the direct physiological effects of physical exercises and the indirect effects of risk factors control, lifestyle modification, and mood. Several studies had shown that patients who underwent CR programs following primary PCI had a lower mortality rate [ 13 , 16 ].…”
Section: Benefits Of Cardiac Rehabilitationmentioning
confidence: 99%
“…Patients frequently do not participate in CR due to their low perception of the program’s importance and necessity. The less optimal participation may lead to less optimal results in CR [ 3 , 16 ].…”
Section: Types Of Cardiac Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation